Association between individual-level socioeconomic factors and intimate partner violence victimisation in women: a systematic review protocol - Lalith Senarathna; Haizana Parween Reyal; Nayomi Dissanayake; Harsha Gunarathna; Dilukshi Soysa; Manoj Sanjeewa Fernando (BMJ Open)
Introduction Intimate partner violence (IPV) is a global public health problem. Although both men and women experience IPV, the burden is more on women. To address IPV effectively, it is important to understand the factors that cause IPV including the socioeconomic factors. However, there is an inadequacy of knowledge on how socioeconomic factors at different levels affect IPV. Hence, the objective is to review the individual-level socioeconomic factors associated with IPV victimisation of women and girls.Methods and analysis The search strategy was developed to identify publications from January 2010 to 30 June 2024. The selected electronic databases of PubMed/MEDLINE, EMBASE, CINAHL, PsycINFO, Web of Science, Scopus and Science Direct will be searched. The eligibility criteria for data collection are based on participants/population (women and girls), exposure (socioeconomic factors) and outcome (IPV). In primary search, the title and abstracts will be screened and reference lists of selected articles will be screened for additional studies. Two researchers will independently screen the articles, and in any disagreements, a third researcher will be consulted. The data will be tabulated to present the study and participant characteristics, comparison descriptors between victims and non-victims, inclusion and exclusion criteria, primary and secondary outcomes data, results, limitations and implications. A quality assessment will be performed on the selected studies to avoid bias. A narrative synthesis will summarise the findings.Ethics and dissemination Ethical approval was waived because only secondary data are used. The protocol will be published, and the findings will be disseminated via publication in a peer-reviewed journal.PROSPERO registration number CRD42022373535.